Can Companies Distributethe Dividends in 2020? Study Case on Theindonesia Stock Exchange (Vallis Aurea, 2024)
This study aims to determine the effect of leverage, liquidity, stock prices, and good corporate governance on dividend distribution. The data used in this study can be found on the Indonesia Stock Exchange website (www.idx.co.id), the websites of each company, and www.investing.com. By using the purposive sampling method, there are 152 manufacturing companies in 2020 that were listed on the Indonesia Stock Exchange before 2019 and had released audited financial statements ending December 31, 2020 and annual reports for the period 2020. Data is analyzed using logistic regression in SPSS version 25. Based on the research that has been done, the results show that leverage and good corporate governance affect dividend distribution, but liquidity and stock prices do not affect dividend distribution.